Anomaly Detection of Pipeline Leakage Based on Electric Field Component Imaging Using Ground Penetrating Radar. (27th June 2022) - Yang, Yang; Du, Zhiyuan; Li, Yanan; Zhang, Tianyu; Liu, Lu; Iqbal, Ibrar; Peng, Sanxi
Abstract : Ground penetrating radar (GPR) is an effective method that can be applied in pipeline leakage detection. However, when the distribution of the underground medium is complex, it becomes difficult to accurately identify the abnormal leakage area directly from the GPR data profile. In this paper, based on the characteristics of high water content in the abnormal leakage area and according to the relationship between the reflected wave coefficient and the dielectric constant, the electric field component imaging technology of GPR data is proposed. Next, the electromagnetic wave responses of geological models with different dielectric parameters are simulated by finite difference time domain (FDTD). It can be seen from the forward modeling results that the greater the difference is in the dielectric constants of the media on both sides of the interface, the stronger the reflected wave energy will be. Finally, the electric field component imaging technology of GPR data is applied to pipeline leakage detection in an industrial area. The test results show that the abnormal area of pipeline leakage appears as a high-amplitude area in the electric field component map.